2001
DOI: 10.1093/emboj/20.21.6095
|View full text |Cite
|
Sign up to set email alerts
|

A specific lysine in c-Jun is required for transcriptional repression by E1A and is acetylated by p300

Abstract: The adenovirus E1A protein regulates transcription of cellular genes via its interaction with the transcriptional coactivators p300/CBP. The collagenase promoter activated by the c-Jun protein is repressed by E1A. Here we show that E1A repression is specific for c-Jun, as E1A does not repress the collagenase promoter activated by the homologous transcription factor EB1. Using chimeras of c-Jun and EB1, we demonstrate that a 12 amino acid region in the basic region of the c-Jun DNA-binding domain is essential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 51 publications
1
71
0
Order By: Relevance
“…The experiments presented are representative of at least three independent experiments. DB) was in vitro acetylated by a GST-tagged p300 acetyltransferase domain in the presence of [ 14 C]acetyl-CoA (21). Subsequently, the reactions were incubated with GST-tagged hSir2 SIRT1 in the absence or presence of the essential cofactor NAD ϩ (24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments presented are representative of at least three independent experiments. DB) was in vitro acetylated by a GST-tagged p300 acetyltransferase domain in the presence of [ 14 C]acetyl-CoA (21). Subsequently, the reactions were incubated with GST-tagged hSir2 SIRT1 in the absence or presence of the essential cofactor NAD ϩ (24).…”
Section: Resultsmentioning
confidence: 99%
“…pcDNA3.1-myc-hSir2 SIRT1 and pRP265-GSThSir2 SIRT1 were created by ligating a BamHI/XbaI fragment from pcDNA3.1-hSir2 SIRT1 into BamHI/XbaI-digested pcDNA3.1-myc and pRP265, respectively. pRc/RSV-CBP-HA and pRP265-GST-p300-HAT were kindly provided by R. Giles (20) and R. Vries (21), respectively. Gal4-DBD-CBP-HA constructs were a kind gift of E. Kalkhoven (22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these observations and extended to c-Fos, we found that SIRT1 directly interacted with the bZIP domain of both c-Fos and c-Jun, resulting in a reduction in the p300-induced acetylation of c-Fos and c-Jun. c-Jun has been reported to be acetylated by CBP/p300 at 271 lysine residues within the basic region of bZIP domain (5), which promoted us to investigate the relationships between the acetylation status of the basic region and SIRT1-mediated transcriptional inhibition. Surprisingly, none of the lysine mutants within the basic region of c-Jun affected AP-1 transcriptional activity in our experiments (data not shown).…”
Section: Sirt1 Is a Nadmentioning
confidence: 99%
“…In addition to direct binding to cis-acting elements, AP-1 could also interact with other transcriptional regulators, participating in transcriptional regulation, and the bZIP domain contributes to the association with co-activator (3) or co-repressor (4). The transcriptional activity of AP-1 is regulated by the post-translational modification, including acetylation (5). The acetylation modification of transcriptional factors changes the proteinprotein or protein-DNA interaction as an important regulatory mechanism of transcription (6).…”
mentioning
confidence: 99%